Bending of DNA duplexes with mutation motifs. (23rd June 2019) - Růžička, Michal; Souček, Přemysl; Kulhánek, Petr; Radová, Lenka; Fajkusová, Lenka; Réblová, Kamila
Abstract: Mutations can be induced by environmental factors but also arise spontaneously during DNA replication or due to deamination of methylated cytosines at CpG dinucleotides. Sites where mutations occur with higher frequency than would be expected by chance are termed hotspots while sites that contain mutations rarely are termed coldspots. Mutations are permanently scanned and repaired by repair systems. Among them, the mismatch repair targets base pair mismatches, which are discriminated from canonical base pairs by probing altered elasticity of DNA. Using biased molecular dynamics simulations, we investigated the elasticity of coldspots and hotspots motifs detected in human genes associated with inherited disorders, and also of motifs with Czech population hotspots and de novo mutations. Main attention was paid to mutations leading to G/T and A+/C pairs. We observed that hotspots without CpG/CpHpG sequences are less flexible than coldspots, which indicates that flexible sequences are more effectively repaired. In contrary, hotspots with CpG/CpHpG sequences exhibited increased flexibility as coldspots. Their mutability is more likely related to spontaneous deamination of methylated cytosines leading to C > T mutations, which are primarily targeted by base excision repair. We corroborated conclusions based on computer simulations by measuring melting curves of hotspots and coldspots containing G/T mismatch.